Improving Precision of Proximity Ligation Assay by Amplified Single Molecule Detection - Ke, Rongqin; Nong, Rachel Yuan; Fredriksson, Simon; Landegren, Ulf; Nilsson, Mats (PLOS ONE, 2013)
Proximity ligation assay (PLA) has been proven to be a robust protein detection method. The technique is characterized by high sensitivity and specificity, but the assay precision is probably limited by the PCR readout. To investigate this potential limitation and to improve precision, we developed a digital proximity ligation assay for protein measurement in fluids based on amplified single molecule detection. The assay showed significant improvements in precision, and thereby also detection sensitivity, over the conventional real-time PCR readout.